The role of education and cultural policies in the construction of european identity - Bozkır, Ayça Bener (My University, 2019)
Avrupa kimliği, din, dil ve ırk ayrımcılığı olmadan, Avrupa kıtasındaki herkesin Avrupa entegrasyonunun bir parçası olarak kabul edildiği anlamına gelir. Tezin konusu, Avrupa kimliğinin oluşturulmasında ve bütünleşme amaçlarına hizmet etmede Avrupa Eğitim ve Kültür Politikaları ile Gençlik ve Eğitim Programının oynadığı roldür. Bu bağlamda, inşaacı yaklaşımın Avrupa kimliğinde oynadığı rol sosyal yapılandırmacı bir bakış açısıyla incelenmiştir. AB için çok önemli olan Avrupa kimliği kavramı birçok faktörden etkilenmiş olsa da eğitim ve kültür Avrupa kimliğinin inşa sürecinde çok önemli role sahiptir. Eğitim ve kültürel politikalarla birlikte, Avrupa kimliği de gelişmeye devam ediyor. “Avrupa Kimliğinin İnşasında Eğitim ve Kültür Politikalarının Rolü” başlıklı bu tez, Avrupa kimliği oluşturma çerçevesinde, Avrupa eğitim ve kültür politikalarının kademeli evriminin kapsamlı bir değerlendirmesini sağlamayı amaçlamaktadır.

European identity, without discrimination of religion, language and race, means that everyone in the European continent is regarded as a piece of the European integration. The subject of the thesis is the role of the European Education and Cultural Policies as well as Youth and Training Program play in constructing European identity and serving the aims of integration. In this context, the role they play in the construction European identity is examined from a social constructivist perspective. The concept of European identity, which is very important for the EU, is influenced by many factors, education and culture have the vital role in the construction process of European identity. European identity continues to develop with the education and cultural policies. This thesis, titled as ‘The Role of Education and Cultural Policies in Construction of European Identity’, aims to provide a comprehensive assessment of the gradual evolution of European education and cultural policies within the framework of European identity creation.
Keywords: Avrupa; Avrupa Birliği; Avrupa Kimliği; Culture; Education; Eğitim; European Identity; European Union; Kültür European